A meshfree unit-cell method for effective planar analysis of cellular beams. (1st April 2017) - Zainal Abidin, A.R.; Izzuddin, B.A.; Lancaster, F.
Highlights: Novel method for planar analysis of cellular beams, as a precursor to accurate local buckling analysis of web components. Proposal of a unit-cell approach, taking advantage of identical cells along beam. Adoption and enhancement of Element Free Galerkin method for application around irregular plates with openings. Development of novel unit-cell super-element formulation utilising flexibility concepts. Realisation of considerable modelling and computational benefits, paving the way for direct application in design. Abstract: This paper presents a novel approach for accurate and efficient planar response analysis of cellular beams, which provides the necessary input for local out-of-plane buckling analysis of web components. The proposed approach utilises the super-element concept defined for unit-cells, achieving further efficiencies through an enhanced Element-Free Galerkin (EFG) approach for establishing the planar super-element response. Several examples are presented, firstly at the level of unit-cells, where the computational benefits of the EFG method are highlighted, and finally at the overall level of cellular beams, where the superior performance of the unit-cell approach with virtually no compromise in accuracy is demonstrated.